Prevalence of Blindness and Cataract Surgical Coverage in Former Lumbini Zone, Nepal: A Rapid Assessment of Avoidable Blindness (RAAB) Study - Thapa, Saraswati Khadka; Chettri, Shital Khattri; Shah, Ranjan (Journal of National Heart and Lung Society Nepal, 2026)
Background: Blindness and visual impairment remain major public health concerns among older adults in Nepal, with cataract being a leading cause of avoidable blindness. This study aimed to assess the prevalence and causes of central vision blindness and visual impairment, as well as cataract surgical coverage among people aged 50 years and older in the Lumbini Zone of Nepal..Methods: A population-based cross-sectional survey was conducted using the Rapid Assessment of Avoidable Blindness (RAAB) methodology. Data were collected using the mRAAB smartphone application and analyzed with the standard RAAB6 software. A total of 3,431 participants aged 50 years and above were examined for visual acuity, causes of visual impairment, and cataract surgical status.Results: The prevalence of bilateral blindness in the better eye was 2.1% (95% CI: 1.5–2.6) with best correction or pinhole and 2.2% (95% CI: 1.5–2.7) with available correction. Severe visual impairment (SVI) affected 3.1% (95% CI: 2.4–3.9) of participants, while moderate visual impairment (MVI) and early visual impairment affected 14.0% (95% CI: 12.1–15.8) and 12.7% (95% CI: 11.0–14.5), respectively. Cataract was the leading cause of blindness, SVI, and MVI. Untreated cataract accounted for a substantial proportion of visual impairment, with males showing higher prevalence of SVI, MVI, and early visual impairment than females. Cataract surgical coverage (CSC) for visual acuity worse than